Full electric helicopter anti-torque - Stoll, M.; Hupfer, C.; Stuckmann, C.; Bichlmaier, S.; Mindt, M.; Seher-Weiss, S.; Hibler, S.; Thielecke, F. (My University, 2022)
On the way to complete electric flight, the electrification of helicopter subsystems is an essential milestone. This paper discusses the design of an electric helicopter anti-torque system, which uses Kopter’s AW09 helicopter as a platform and shall be tested in ground tests. Analysis of state of the art anti-torque devices for helicopters has helped to identify concepts, which are suitable to be combined with electric propulsion and actuation. Engineering models are used to estimate the power benefits of varied tail rotor RPM, enlarged and steerable vertical stabilizers and drag reducing devices, which cover the rotor in forward flight. In connection with operational benefits viewed from the OEMs perspective, an architecture is proposed which consists of an electric driven shrouded tail rotor, an electric pitch actuation system and additional aerodynamic surfaces, like a steerable vertical stabilizer and a drag optimized tail rotor cover. The systems were developed according to the results of a safety analysis to meet the requirements of CS-27. The electric tail rotor drive is designed with an internal level of redundancy that allows to compensate for subsystem failures.